Evaluación del impacto de la rebaja por la deducción de gastos personales de las personas naturales bajo relación de dependencia en el pago del Impuesto a la Renta en el ejercicio fiscal 2022 - Ponce Ochoa, José Luis (2024)
Tax policy, as part of a government's public policies, plays a crucial role in the economy and social well-being of the population. This study closely examines the impact of the application of the Organic Law for Economic Development and Fiscal Sustainability after the COVID-19 Pandemic on the calculation of Income Tax on natural persons. The objective was to evaluate the impact of the reduction due to the deduction of personal expenses of natural persons under a dependency relationship in the payment of Income Tax in fiscal year 2022. The difference-in-differences econometric method was used in the methodology, recommended by the National Planning Secretariat of Ecuador for impact evaluations, which made it possible to objectively determine to what extent it affected the family economy in the individuals analyzed as well as the use of quantitative methods to determine the impact on the General Budget of the State (PGE in Spanish). The findings reveal that the collection of Income Tax in these taxpayers in 2022 increased by 86% compared to 2021, causing a considerable impact on the taxpayers' pockets. However, a small increase in PGE total income is evident. These measurements are important, because they numerically demonstrate the growth in tax collection and share of total revenue from the proforma budget. The impact of this change in the law on individuals in a dependent employment relationship was determined by evaluating how many U.S. dollars were affected. For these individuals, the only deductible expense, apart from contributions to social security, is personal expenses.